Budget Execution in Health : Concepts, Trends and Policy Issues - Piatti-Funfkirchen, Moritz; Barroy, Helene; Pivodic, Fedja; Margini, Federica (World Bank, Washington, DC, 2021)
Most countries are committed to the provision of quality health services to all, without risk of financial hardship. Adequate budget provisions are an important, yet insufficient requirement in this pursuit. The budget also needs to be implemented in full and with regard to efficiency and accountability. While this is widely acknowledged, there is no systematic evidence on how well the health budget is implemented and literature remains thin on how budget execution practices relate to health financing functions and service delivery. This report is the first in a series of publications on the topic following an active World Health Organization and World Bank collaboration. It aims to define concepts, characteristics and trends in health sector budget execution. The report first calls for clarity in use of terminology. It helps to differentiate between ‘budget execution rates’ and ‘budget execution practices’. The former refers to the share of the budget being executed. The latter to processes on how well the budget is executed. Both aspects are equally important. Not implementing the budget in full is a lost opportunity, efficiency and accountability concern and undermines the health sector’s ability to deliver services. It also undermines prospects for increased fiscal space going forward. To identify trends and patterns in over and underspending, the report draws on previously unexplored PEFA annex and World Bank BOOST data. This reveals the following: Health budget execution rates are inversely related to levels of income and maturity of PFM systems. Health budget under-execution is particularly pervasive in LMICs where the budget is executed at around 85-90 percent. Some countries have chronic budget execution problems where the budget is executed at a rate below 85 percent across consecutive years. In LMICs, the health budget is systematically implemented at a lower rate than the general government budget. This means, that governments are effectively deprioritizing health during budget implementation. For Sub-Saharan Africa countries in the sample, the average health budget was 6.7 percent of the general government budget. Health spending as a share of general government spending was half a percentage point less at 6.2 percent. In some countries this is much more pronounced, where health is deprioritized by 2-3 percentage points of general government spending during implementation. The health budget was also implemented at a lower rate than the education budget in most countries at an average rate of 4 percentage points. Underspending in some categories often occurs concurrently with overspending on other expenditure items. While the wage and salary budget tend to be implemented in full, this is less so for goods and services or the capital budget. This can leave health workers without the necessary supplies or support infrastructure to provide quality services and invariably lead to inefficiencies.